Recording using a motion capture system and a mobile device with synchronization of the recording triggering - Walczyna, Karol; Jasiński, Bartosz; Smołka, Jakub; Miziołek, Mateusz (Journal of Computer Sciences Institute, 2019)
The main problem during research with a motion capture system and mobile device is lack of possibility to simultaneously begin recording on the motion capture system and a mobile device. Two methods were developed to solve this problem. In the first method the recording is started on the mobile phone and the motion capture system is notified, in the second method the motion capture system starts recording and notifies the mobile device. Both of them were compared for lags and correlation of data form the mobile device and the motion capture system.